Evolution of residual strain and strain energy in rocks under various types of uniaxial cyclic loading-unloading - Liu, Zhixi; Liu, Xiaodie (Frontiers in Earth Science, 2023)
In the process of roadway excavation, the rock mass around the roadway is often subjected to cyclic loads, and the rock mechanical properties and strain energy evolution under cyclic loads are obviously different from those under compression, so it is urgent to carry out research on rock mechanical properties and strain energy evolution under cyclic loads. This study aims to investigate the evolution of residual strain and strain energy in rocks under uniaxial cyclic loading-unloading experiments (UCLUE). Four types of rocks, namely coal, white sandstone, red sandstone, and granite, were subjected to uniaxial compression experiments (UCE) and various uniaxial cyclic loading-unloading experiments (UEACLUE). The findings are as follows: analysis of UEACLUE revealed a gradual decrease in residual strain with an increasing number of cycles, leading to its eventual disappearance. However, if the cyclic loading-unloading (CLU) was continued beyond this point, the rocks displayed a reappearance of residual strain. The number of cycles required to eliminate residual strain was found to be inversely proportional to the peak strength of the rocks, while directly proportional to the upper limit value of UCLUE. Among the different stages of the uniaxial cyclic loading and unloading test, the plastic stage of white sandstone exhibited the largest disparity in dissipated strain energy, followed by the plastic stage of red sandstone, with coal displaying the smallest difference. Analysis of dissipated strain energy in the four types of uniaxial cyclic loading and unloading tests revealed differences of 0.00348 mJ▪mm−3, 0.03488 mJ▪mm−3, 0.02763 mJ▪mm−3, and 0.01619 mJ▪mm−3 in the plastic stage for the respective rock types. Furthermore, examination of the input strain energy density (ISED) and dissipated strain energy density (DSED) during the CLU process showed a linear relationship between these variables. Additionally, the investigation of ISED and DSED in other types of UCLUE demonstrated adherence to the cyclic-linear dissipation law (CLDL). The study of mechanical properties and strain energy evolution under CLU is of positive significance for the development of rock fatigue damage and rock damage mechanics.